Hybrid Natural Fibre Polymer Composites: A Comprehensive Review - Bachtiar, Dandi; Zulfan, Zulfan; Munawir, Al (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2025)
Hybrid natural fibre polymer composites (HNFPCs) have emerged as an innovative and sustainable alternative to conventional fibre-reinforced composites, driven by the need for eco-friendly, lightweight, and high-performance materials. This review presents a comprehensive analysis of recent advancements in HNFPCs, focusing on material constituents, fabrication techniques, resulting properties, and industrial applications. Various hybrid systems, including natural–natural and natural–synthetic fibre combinations, are explored for their synergistic potential in improving mechanical strength, thermal stability, and moisture resistance. The influence of surface modification methods and processing parameters on the interfacial bonding and durability of composites is critically discussed. A comparative evaluation of key physical and mechanical properties is provided using recent literature (2020–2024), highlighting performance trends across different hybrid configurations. Applications in automotive, aerospace, construction, marine, and consumer product sectors demonstrate the industrial relevance of HNFPCs, with an emphasis on sustainability and regulatory compliance. Despite their promise, challenges remain in property variability, limited thermal performance, and recyclability. Future perspectives suggest that integrating bio-based matrices, advanced treatments, and data-driven design will be essential in advancing the next generation of multifunctional, green composites. This review aims to provide a valuable resource for researchers and industry stakeholders seeking to optimize the development and deployment of HNFPCs for structural and semi-structural applications.